2007
DOI: 10.1152/ajpendo.00216.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transient PTH on early proliferation, apoptosis, and subsequent differentiation of osteoblast in primary osteoblast cultures

Abstract: In primary calvarial osteoblast cultures derived from transgenic mice expressing green fluorescent protein (GFP) under the control of 3.6-kb Col1a1 promoter, the emergence of GFP signal marks the transition of multipotential osteoprogenitors into preosteoblasts. Early transient treatment (days 1-7) of these cultures with parathyroid hormone (PTH) has an anabolic effect that is not associated with an increase in total DNA content or cell number in day 21 cultures. In the present study, the effect of early PTH t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…It is the accumulation of repeated new waves of osteoprogenitors with enhanced osteogenic potential that mediates the PTHstimulated increase in bone mass [28,32]. This may also explain that the observed lag period before the enhanced PTH-induced bone formation phase is initiated in the Nmp4-null mice.…”
Section: Nmp4 and Pthmentioning
confidence: 97%
See 2 more Smart Citations
“…It is the accumulation of repeated new waves of osteoprogenitors with enhanced osteogenic potential that mediates the PTHstimulated increase in bone mass [28,32]. This may also explain that the observed lag period before the enhanced PTH-induced bone formation phase is initiated in the Nmp4-null mice.…”
Section: Nmp4 and Pthmentioning
confidence: 97%
“…PTH did not significantly impact the number of CFU-F AlkPhos + colonies recovered from the BM of either genotype, although there was a trend toward modestly elevating the frequency of these cells. A variety of studies have shown conflicting stimulatory and inhibitory effects of PTH on osteoprogenitor proliferation [28][29][30]; however, the WT and null mice were treated with intermittent PTH or vehicle for 3 weeks (number of mice/experimental group = 10-14). A 2-factor ANOVA was used to evaluate the impact of genotype and treatment on the individual parameters.…”
Section: He Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The PTH stimulates bone formation by increasing the number of osteoblasts [Wang et al 2007]. The PTH effects are mediated by a G-protein-coupled receptor, the PTH receptor 1 [Maeda et al 2013;Van Der Lee et al 2013].…”
Section: Pth-related Therapiesmentioning
confidence: 99%
“…However, constant application of PTHrP in chondrogenic medium suppressed chondrogenesis instead of selectively inhibiting hypertrophic features only [6,18]. Interestingly, PTH can exert opposing effects on the osteogenic differentiation of osteoblasts [19,20], rat MSCs [21], and on bone mass dependent on a constant versus intermittent application regime. Whereas constant application acted catabolically on bone, an intermittent application (eg, once daily) provided anabolic effects, resulting in a net increase in bone mass [22,23].…”
mentioning
confidence: 99%